1972
DOI: 10.1136/gut.13.1.31
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intravenous metoclopramide on gastrooesophageal reflux

Abstract: SUMMARY The effect of intravenous metoclopramide was studied radiologically in 40 patients with gastrooesophageal reflux. In no patient was reflux significantly diminished.Metoclopramide activates gastrointestinal motility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
1

Year Published

1973
1973
1976
1976

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 9 publications
0
1
1
Order By: Relevance
“…The rise in tone of the lower oesophageal sphincter presumably assists in preventing reflux, while the increased pressure of peristaltic contractions may assist oesophageal emptying. Our findings conflict with those of Glanville and Walls (1972) who, using standard radiological techniques, found that intravenous metoclopramide failed to change the incidence of 2* gastrooesophageal reflux during barium meal examinations. The reason for the difference probably lies in the methodology.…”
Section: Discussioncontrasting
confidence: 99%
“…The rise in tone of the lower oesophageal sphincter presumably assists in preventing reflux, while the increased pressure of peristaltic contractions may assist oesophageal emptying. Our findings conflict with those of Glanville and Walls (1972) who, using standard radiological techniques, found that intravenous metoclopramide failed to change the incidence of 2* gastrooesophageal reflux during barium meal examinations. The reason for the difference probably lies in the methodology.…”
Section: Discussioncontrasting
confidence: 99%
“…A statistical association has been demonstrated between the intraluminal high pressure zone (HPZ) at the cardia and gastrooesophageal reflux (Winans and Harris, 1967;Thurer, DeMeester, and Johnson, 1974). Many hormones and drugs have been shown to affect this high pressure zone, but no concomitant change in reflux status has been reported (Glanville and Walls, 1972;Moossa, Cooley, and Skinner, 1973).…”
mentioning
confidence: 99%